Ordbogsanmeldelser i LexicoNordica - Bergenholtz, Henning (LexicoNordica, 2003)
Dictionary criticism is undoubtedly an important part of lexicography. It is important both in terms of developing lexicographical theory and improving lexicographical practice. According to Wiegands basic theory (Wiegand 1989), dictionary criticism even formsone of the four pillars of theoretical lexicography (besides user research, dictionary historiography and systematic dictionary research). In the case of scientific credit, i.e. the scientific importance of criticism, however, this perspective is not uniformly shared by all members of the academic world. The editorial committee of this scientific journal has pointed out very clearly the importance of dictionary criticism in relation to lexicography. In this contribution, I will make a few remarks about reviewing in general and give a quantitative and qualitative overview of the 104 reviews and 6 answers to reviews published in the first nine volumes of LexicoNordica.